ANALISIS PENGARUH BUDAYA ORGANISASI, KEPUASAN KERJA, DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN (Studi pada Karyawan Kantor PT. Telekomunikasi Indonesia Tbk. Divisi Regional IV Jawa Tengah dan Daerah Istimewa Yogyakarta) - Prawira, Samuel Jaka; Darmastuti, Ismi (Faculty of Economics and Business Diponegoro University, 2015)
The key of organization’s success is generated by each of the resources of the organization. It can be said that human resources is one of the determining factors for winning the business competition in a short period and long term. The human factor is not only the holders of an important role for the organization, but also a vital tool for organizations because it can not be replaced completely by other resources. The business competition today is requiring the role of human resources to have a competitive advantage and an organization should be able to improve the employee’s performance.This research aims to analyze the effect of variables of organizational culture, job satisfaction and organizational commitment on employee performance. This research was conducted at PT Telkom Indonesia, Tbk Regional IV Jateng- DIY. The number of samples specified by set as much as 76 respondents using Convenience sampling methods and Methods data analysis used was multiple linear regression analysis using SPSS.The results of testing againts the hypothesis, indicating that organizational culture variable has positive influence on employee’s performance. Job satisfaction variable has positive influence on the employee’s performance, and organizational commitment variable has positive influence on employee’s performance.